What is new in the 2018 Chinese hypertension guideline and the implication for the management of hypertension in Asia? - Wang, Ji Guang; Chia, Yook Chin; Chen, Chen Huan; Park, Sungha; Hoshide, Satoshi; Tomitani, Naoko; Kabutoya, Tomoyuki; Shin, Jinho; Turana, Yuda; Soenarta, Arieska Ann; Tay, Jam Chin; Buranakitjaroen, Peera; et al. (Wiley, 2020)
The new Chinese hypertension guideline comprehensively covers almost all major aspects in the management of hypertension. In this new guideline, hypertension remains defined as a systolic/diastolic blood pressure of at least 140/90 mm Hg. For risk assessment, a qualitative approach is used similarly as in previous Chinese guidelines according to the blood pressure level and the presence or absence of other risk factors, target organ damage, cardiovascular complications, and comorbid diseases. The therapeutic target is 140/90 mm Hg in general, and if tolerated, especially in high-risk patients, can be more stringent, that is, 130/80 mm Hg. However, a less stringent target, that is, 150/90 mm Hg, is used in the younger (65-79 years, if tolerated, 140/90 mm Hg) and older elderly (≥80 years). Five classes of antihypertensive drugs, including β-blockers, can be used either in initial monotherapy or combination. The guideline also provided information on the management of hypertension in several special groups of patients and in the presence of secondary causes of hypertension. To implement the guideline recommendations, several nationwide hypertension control initiatives are being undertaken with new technology. The new technological platforms hopefully will help improve the management of hypertension and generate scientific evidence for future hypertension guidelines, including a possible Asian hypertension guideline in the near future. © 2020 Wiley Periodicals, Inc.